Milk fermentation and making of syrup using microflora as the constituen of yogurt starter - . Dzarnisa; . Yurliasni (Syiah Kuala University, 2012)
Fermented milk is one of important source of human nutrition, but not every one able to digest it properly, which can cause lactose intolerance. One alternative solution is milk should be fermented. Lactose in milk is broken down into glucose and galactose by the starter culture activity and decrease the digestion problem. There are milk based syrup which is potential to be improved in Indonesia as diversification product of fermented milk. Research has been conducted in Milk Processed Laboratory, Agriculture Department, of Syiah Kuala University. The experiment divided in to two phase which were 1) to determine milk fementation process by different pecentage of bacteria and 2) making syrup by adding sugar in fermented milk. Completely Random Disigned (CRD) was used based on sugar and yoghurt ratio in several species of microflora. namely Lactobacillus bulgaricus, Lactobacillus acidophillus and Streptococcus thermophillus. Te result of the first phase showed that milk completely fermented by adding 5 percent of bacteria and significantly (p0,05)effect the pH, lactic acid level and unsignificantly effect fat and protein level. In the second phase showed that the best syrup performance is 50 percent fermented milk added with 5 percent sugar. The addition of different percentage of starter very significantly (P0,01) effect on pH, lactic acid level and also effect hedonic test. Furthermore, that treament given did not effect any of fat, protein, colour and aroma. In conclusion, percetage of sugar and starter addition will influence the flavor of fermented milk syrup